Risks of Cancer Associated with Therapeutic Drugs for Inflammatory Bowel Disease - Won Moon; Jae Jun Park (The Korean Journal of Gastroenterology, 2024)
Crohn's disease and ulcerative colitis are lifelong chronic inflammatory conditions, with many patients requiring ongoing immunomodulatory drug therapy for maintenance treatment. Recent therapeutic goals in inflammatory bowel disease (IBD) are not only aimed at symptomatic remission but also at achieving mucosal healing to improve the natural course of the disease. In this context, therapeutic approaches are being applied in clinical settings that involve early and appropriate use of drugs, such as immunomodulators or biologics, that have the potential to induce healing of the inflamed intestine before irreversible intestinal damage occurs. All drugs that continuously control intestinal inflammation in IBD can heal the mucosa and potentially reduce the incidence of colitis-associated bowel cancer; however, the continuous use of immunosuppressants can potentially increase the risk of malignancies. The safety issues of the drugs used in clinical practice are partly confirmed during their development processes or shortly after initial marketing, but in other cases, they are estimated through post-marketing case reports or epidemiological studies, sometimes decades after drug approval. This review explores the risks associated with malignancies related to the treatment of IBD, focusing on drugs currently approved in Republic of Korea.